103. Nerve ultrasound findings in neuropathy associated with anti-mag antibodies. Issue 1 (January 2015) - Padua, L.; Lucchetta, M.; Granata, G.; Luigetti, M.; Campagnolo, M.; Torre, C. Dalla; Coraci, D.; Sabatelli, M.; Briani, C.
<x xml:space="preserve">Abstract</x> We studied patients with neuropathy and anti-myelin-associated glycoprotein antibodies nerve ultrasound (US). 28 patients with anti-MAG neuropathy underwent nerve US. Echotexture, nerve cross sectional area (CSA), intra-nerve and inter-nerve CSA variability were assessed. Patients with IgM paraproteinemic neuropathy without anti-MAG antibodies and with chronic inflammatory demyelinating polyradiculoneuropathy (CIDP) associated with IgM paraprotein were studied as controls. US findings were correlated with disease duration and clinical severity (INCAT disability score). 26/28 patients had increased CSA (23 at atleast one nerve outside entrapment sites). Intra-nerve CSA variability was abnormal in 21/28 patients (in 14 for increased nerve CSA outside entrapment sites). Inter-nerve CSA variability was abnormal in 16 patients (in half of whom for CSA increase out of entrapment sites). No correlation was found between US findings and INCAT disability score or disease duration. Patients with IgM paraproteinemic neuropathy without anti-MAG antibodies had similar US abnormalities. Instead 4/5 patients with CIDP and IgM paraprotein presented significant and diffuse nerve CSA enlargement. The US findings in anti-MAG antibody neuropathy, different from those of CIDP, might express the diverse pathogenic mechanisms and contribute to diagnosis in atypical cases.